Comparison of corn yield, water use efficiency (WUE), and growth under different tillage systems and fertilizer inputs - Amin Fathi; Davood Barari Tari; Hormoz Fallah Amoli; Yousef Niknejad (Agrisost, 2023)
Context: Corn is one of the four most important cereals in the world after wheat and rice. Nitrogen and various tillage systems are important factors in improving the traits and performance of corn. Sustainable agriculture requires improvements in soil tillage management and more efficient application of fertilizers as agricultural resources.